P20 Parental understanding of concussion in youth rugby is significantly improved by viewing the RFU concussion education video. Issue 3 (14th February 2019) - Samuel, T; Aquilina, K; Dawes, W
Abstract : Objectives: To investigate the current understanding parents have of concussion in their rugby-playing children aged 9–17. Design: Cross-sectional study Subjects: 86 parents from four clubs completed an online questionnaire Methods: Areas covered (1) Parental experience of concussion (2) Rate of viewing of the RFU concussion educational video (RFUCEV), (3) Identification of symptoms of concussion (4) Understanding of the risk of concussion. Each participant was given a composite score, out of 19, based on their performance in symptom identification and true/false questions. Independent-sample two-tailed t-tests were conducted to analyse scores, primarily controlling for viewing of the RFUCEV Results: There was a significant difference in the scores between the group that had viewed the RFUCEV (n=32, M=14.75, SD=2.55) and those who had not (n=54, M=13.05, SD=2.87); t(84)=2.75, p=0.00721. Additionally, over 25% of parents reported that their child had suffered a concussion, and this was also found to significantly improve the awareness score (p=0.04678) Conclusions: Statistically significant improvement in composite scores after viewing the RFUCEV makes it reasonable to require compulsory parental education prior to signing up a child to play rugby. This would build on the protocol changes made by the RFU in 2014 and further progress the safety of the sport. We suggest the video be improved to emphasise the areas highlighted as inadequately understood, including the increased risk of concussion in under-18s compared to adults.